The Role of Ulama in Countering Boko Haram Insurgency: A Pattern of the Al-Azhar ‘Ulama - Rabiu Shehu Muhammad; Aminu Umar (International Journal Ihya' 'Ulum al-Din, 2021)
The eruption of Boko Haram and its insurgency in 2009 caused the loss of life and property that is unprecedented in northern Nigeria's history since independence. Various tools and approaches have been used in analyzing a phenomenon with a view to offering solutions to it. People from various walks of life including professionals and experts have expressed their views and opinions about groups, their activities and ways to limit them. Since the group is rightly or wrongly associated and identified with Islam in its activities, experts especially the ulama analyze the group from an Islamic perspective using the Qur'an and Sunnah and the actions of the salaf as their basis for offering solutions. to group problems. With this background, this paper examines the role of Ulama in dealing with the imbroglio of Boko Haram by using the Ulama model of Al Azhar University in particular. The historical method was adopted with data mostly collected from printed materials and the internet. This paper recommends among other things that our scholars should follow some of the approaches used by Al'azhar scholars in eliminating the influence of extremist and rebel groups. .